A Numerical Study on the Influence of an Asymmetric Arc on Arc Parameter Distribution in High-Current Vacuum Arcs - Zaiqin Zhang; Yue Bu; Chuang Wang; Qingqing Gao; Chi Chen (Energies)
During high-current vacuum arcing, asymmetric arcing with off-center plasma columns may occur due to stochastic discharge initiation and mechanical motion, receiving less research attention than symmetric arcing. The objective of this paper is to numerically analyze the influence law of asymmetric arc ignition on arc parameters. For 60 mm diameter contacts, three arc conditions of symmetric arcing, 33% arc offset, and 67% arc offset were modeled. The results show that the arc offset causes asymmetry in the arc’s distribution. For 33% offset, the pressure and number density on the side away from the root of the arc is about 50% of root values, while these parameters fall below 20% for the 67% offset. Simultaneously, arc offset elevates peak parameter values: under 33% offset, maxima for ion pressure, ion density, ion temperature, electron temperature, and current density rise 12%, 11%, 6%, 6%, and 14% versus symmetric arcing; during 67% offset, these escalate significantly to 67%, 61%, 12%, 18%, and 47%. This study contributes to providing reference for the analysis of vacuum interruption processes under asymmetric arcing conditions.